Strategi Komunikasi Pemerintah Desa Sebagai Langkah Taktis Penanganan Dan Pencegahan Covid-19 - Gamaputra, Gading; Prasetyawan, Agus; Isbandono, Prasetyo; Lestari, Yuni; Fitria Putri, Alvionita; Hidayatullah, M Syarif; Noviyanti (Fakultas Ilmu Administrasi Universitas Dr. Soetomo, 2021)
The increase in cases of Corona Virus Disease 2019 (covid-19) has led the Central Government to the Village Government to issue regulations regarding covid-19. Implementation of handling and preventing Covid-19 using a communication strategy canalizing techniques. The trick is to gather various village stakeholders and village organizations to form a Task Force and Volunteer. The task force and volunteers have the goal of inviting the community to carry out a joint movement in breaking the chain of spreading Covid-19. The Covid-19 Task Force and volunteers also formed a posyandu for youth groups and health cadres consisting of mothers. Stakeholders such as village officials, village consultative bodies, youth organizations, youth mosques, task forces and the Health team, through coordination meetings, produced several programs as a step to accelerate the spread of covid-19. Programs such as spraying disinfectants, counseling on healthy living habits, socializing the handlers of covid-19, implementing physical distancing, handling covid-19 posts, distributing cloth masks, and making isolation rooms. The communication strategy used by Kesamben Village has proven successful in inviting the community to prevent the acceleration of the spread of Covid-19 and to increase public awareness of the importance of implementing health protocols. Increasing public awareness such as using masks when leaving the house as a habit, applying physical distancing and adopting clean and healthy living habits. This type of research used in this research is descriptive qualitative, the researcher uses interview techniques, observation and documentation.